Human albumin use at hospitals in the Metropolitan Region of Rio de Janeiro, Brazil Uso de albumina humana nos hospitais da Região Metropolitana do Estado do Rio de Janeiro, Brasil - Guacira Corrêa de Matos; Suely Rozenfeld; Monica Martins (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The study analyzes the use of human albumin in hospitals in Rio de Janeiro, Brazil, using inpatient data from the information system of Brazil's health system between 1999 and 2001. Death was the main outcome as patients died in 32% of admissions in which human albumin was used as compared with 4% of all admissions in the same period and region. The Charlson Comorbidity Index was included for risk adjustment. Human albumin was used in 10,111 in-patients more than 1 year old. 87,774 50-ml bottles of 20% human albumin were consumed at a cost of US$ 1,755. The main diagnoses were neoplasms (29.1%), diseases of the digestive system (17.5%) and circulatory system (16%). Death rate increased with age, public ownership of the hospital, clinical services (as opposed to surgical services), length of stay and use of intensive care. Death was associated with use of more than four bottles of human albumin (PR: 1.30; 99%CI: 1.23-1.37), adjusted for severity and speciality. The results are cause for concern as they may be related to poor compliance with guidelines, excess of risk to patients and unnecessary expenses for the public health system. O estudo analisou o uso da albumina humana em hospitais do Rio de Janeiro, Brasil, utilizando os registros do Sistema de Informações Hospitalares do Sistema Único de Saúde (SIH/SUS), 1999 e 2001. Como 32% das internações resultaram em óbito, em comparação com 4% de óbito para todas as internações no mesmo período e região, este foi o desfecho principal do estudo. A albumina humana foi usada em 10.111 internações de maiores de um ano, que consumiram 87.774 frascos - 50mL a 20%, com gasto de US$ 1.755,00. Os principais diagnósticos foram neoplasias (29,1%), doenças do aparelho digestivo (17,5%) e do aparelho circulatório (16%). Houve maior proporção de óbitos de pacientes mais idosos, que receberam mais doses de albumina humana, internados por mais tempo, em especialidades clínicas, em UTI, em hospitais públicos. O óbito esteve associado ao uso de mais de quatro frascos de albumina humana (RP: 1,30; IC99%: 1,23-1,37), ajustado por gravidade e especialidade. Os resultados evidenciam a baixa adesão aos protocolos, o excesso de risco para os pacientes e os gastos desnecessários para o sistema público de saúde.